Quantitative shadowgraphy for laser–plasma interactions. (15th March 2016) - Boné, A; Lemos, N; Figueira, G; Dias, J M
Abstract: A new all optic non-perturbative diagnostic for measuring densities of long plasma structures is presented. A model based on the refraction of a laser beam crossing a cylindrical column of plasma with a Gaussian density profile is derived and used to measure plasma electronic densities. The model shows good agreement with the performed ray tracing simulations. Experimental measurements of the electronic density of plasma columns ranging from 2 to cm −3 are presented and show good agreement when compared to interferometry measurements.